Bridging the gaps: uncovering the information needs of female students in two nigerian specialised universities - Emiri, Ogochukwu T.; Ijiekhuamhen, Osaze Patrick (Communicate: Journal of Library and Information Science, 2025)
The study examined the information needs of female students at the Federal University of Petroleum Resources, Effurun (FUPRE), and the Nigerian Maritime University, Okerenkoko (NMU) both in Delta State, Nigeria. The study adopted a descriptive survey research design. The total population of female students from both institutions is 3120. Nwanna’s (1981) sampling approach was used to select 10% of the total population which amounts to 312 female students used for the study. The instrument used for eliciting data from the respondents was a structured questionnaire. Data collected using the questionnaire was analyzed using the descriptive statistics method. The findings revealed that academics (100%), accommodation (100%), and finance (100%), among others were classified as the pressing information needs of the female students in FUPRE and NMU examined. The findings also revealed that electronic resources (100%), internet sources (100%), and textbooks (99%), among others, were the top-ranking preferred information sources indicated by the female students examined. The findings showed that the female students use information for meeting their academic (100%) and accommodation aspirations (100%), getting finance sources (98%), and better hygiene (97%) among others. The findings revealed that epileptic power supply (100%), high cost of data (100%), inadequate bandwidth/ poor internet (98%), inadequate finance (95%), and inadequate time (82%), among others, were the pressing challenges affecting the access and use of information by the female students in FUPRE and NMU. It was recommended that alternative power sources and swift internet access should be made available to enhance the information seeking of female students in universities.